Effect of speed manipulation on the control of aperture closure during reach-to-grasp movements - Rand, Miya K.; Squire, Linda M.; Stelmach, George E. (Experimental brain research, 2006)
This study investigates coordination between hand transport and grasp movement components by examining a hypothesis that the hand location, relative to the object, in which aperture closure is initiated remains relatively constant under a wide range of transport speed. Subjects made reach-to-grasp movements to a dowel under four speed conditions: slow, comfortable, fast but comfortable, and maximum (i.e., as fast as possible). The distance traveled by the wrist after aperture reached its maximum (aperture closure distance) increased with an increase of transport speed across the speed conditions. This finding rejected the hypothesis and suggests that the speed of hand transport is taken into account in aperture closure initiation. Within each speed condition, however, the closure distance exhibited relatively small variability across trials, even though the total distance traveled by the wrist during the entire transport movement varied from trial to trial. The observed stability in aperture closure distance across trials implies that the hand distance to the object plays an important role in the control law governing the initiation of aperture closure. Further analysis showed that the aperture closure distance depended on the amplitude of peak aperture as well as hand velocity and acceleration. To clarify the form of the above control law, we analyzed four different mathematical models, in which a decision to initiate grasp closure is made as soon as a specific movement parameter (wrist distance to target or transport time) crosses a threshold that is either a constant value or a function of the above-mentioned other movement-related parameters. Statistical analysis performed across all movement conditions revealed that the control law model (according to which grasp initiation is made when hand distance to target becomes less than a certain linear function of aperture amplitude, hand velocity, and hand acceleration) produced significantly smaller residual errors than the other three models. The findings support the notion that transport-grasp coordination and grasp initiation is based predominantly on spatial characteristics of the arm movement, rather than movement timing.